(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
This paper is aimed at survey of the EM radiations from GSM masts around residential and office areas of Kaduna metropolis. It’s focused on carrying out study on the electromagnetic exposure emitted by mobile phone base stations. Mast from each of the service providers were surveyed (AIRTEL, ETISALAT, GLO, MTN). Radio frequency Electromagnetic Force (RF EMF) strength meter was used to obtain readings from around the mast. The Electric field strength E and magnetic field strength Hwas measured at 0, 8, 16, 24, 32, 40m away from the mast in N/C andT respectively.The readings obtained were analyzed and compared with the International Commission on Non-ionizing Radiation Protection (ICNIRP) and the Institute of Electrical and Electronic Engineers (IEEE) exposures limits for radio frequency waves. The results showed that electromagnetic exposures from the mast are quite below the exposure limits. This research workhasestablished that the populations in Kaduna metropolis are less subjected to any adverse health effects emanating from the Global System of telecommunication masts.